The effect of carbohydrate ingestion on the interleukin-6 response to a 90-minute run time trial - Robson-Ansley, P. J.; Barwood, M.; Eglin, C.; Ansley, L. (International Journal of Sports Physiology and Performance, 2009)
Fatigue is a predictable outcome of prolonged physical activity; yet its biological cause remains uncertain. During exercise, a polypeptide messenger molecule interleukin- 6 (IL-6) is actively produced. Previously, it has been demonstrated that administration of recombinant IL-6 (rhIL-6) impairs 10-km run performance and heightened sensation of fatigue in trained runners. Both high carbohydrate diets and carbohydrate ingestion during prolonged exercise have a blunting effect on IL-6 levels postendurance exercise. We hypothesized that carbohydrate ingestion may improve performance during a prolonged bout of exercise as a consequence of a blunted IL-6 response. Seven recreationally trained fasted runners completed two 90-min time trials under CHO supplemented and placebo conditions in a randomized order. The study was of a double-blinded, placebo-controlled, cross-over study design. Distance covered in 90 min was significantly greater following exogenous carbohydrate ingestion compared with the placebo trial (19.13 ± 1.7 km and 18.29 ± 1.9 km, respectively, p = .0022). While postexercise IL-6 levels were significantly lower in the CHO trial compared with the placebo trial (5.3 ± 1.9 pg/mL and 6.6 ± 3.0 pg/mL, respectively; p = .0313), this difference was considered physiologically too small to mediate the improvement in time trial performance.